0588 REM Sleep Is Associated With Blood Pressure In Mild To Moderate But Not In Severe Obstructive Sleep Apnea. (12th April 2019) - Tang, Xiangdong; Zhang, Ye; Ren, Rong; Yang, Linghui; Tan, Lu; Li, Taomei
Abstract: Introduction: Rapid eye movement (REM) sleep is a state of autonomic instability, dominated by significant fluctuations between the parasympathetic and sympathetic nervous system. As a result of cortical desynchronization during REM, the cardiovascular and respiratory system become more unstable. Repetitive asphyxia events in obstructive sleep apnea (OSA) could result in brain arousal, intermittent hypoxemia during sleep, and abnormalities of REM sleep. Whether the abnormalities of REM sleep in OSA are associated with an abnormal blood pressure have not been explored. Methods: A total of 11218 patients with apnea-hypopnea index ≥ 5/h were included in this study (83.7% males, mean age = 45.06 ± 12.05 years). All patients underwent an overnight PSG. OSA patients were divided into two groups based on the OSA severity (mild to moderate OSA (n=4139), and severe OSA (n=7079)). Hypertension was defined based either on direct blood pressure measures or on diagnosis by a physician. Results: Multiple linear regression analysis revealed that Decreased percentage of REM sleep was significantly associated with an increase in systolic blood pressure in mild to moderate (β= -0.046, p=0.002) but not in severe OSA (β= -0.017, p=0.136). Percentage of REM sleep was not associated with diastolic blood pressure in mild to moderate (β= -0.018, p=0.253) and in severe OSA (β= 0.002, p=0.860), respectively. Logistical regression analysis did not find a significantly association of percentage of REM sleep with hypertension. These results were independent of major confounding factors such as sex, age, body mass index, tobacco, alcohol drinking, coffee use, sleep efficiency and subjective daytime sleepiness, apnea hypopnea index and nocturnal oxygen desaturation. Conclusion: We conclude that decreased REM sleep is associated with increased SBP in mild to moderate but not in severe OSA patients, indicating the association between REM sleep and blood pressure moderated by OSA severity. Support (If Any): This work was supported by the National Natural Science Foundation of China (81530002 81770087).